Exploring the characteristics and most bothersome symptoms in MECP2 duplication syndrome to pave the path toward developing parent‐oriented outcome measures. Issue 8 (15th June 2022) - Ak, Muharrem; Suter, Bernhard; Akturk, Zekeriya; Harris, Holly; Bowyer, Kristina; Mignon, Laurence; Pasupuleti, Sasidhar; Glaze, Daniel G.; Pehlivan, Davut
Abstract: Background: MECP2 Duplication Syndrome (MDS), resulting from the duplication of Xq28 region, including MECP2, is a rare disorder with a nascent understanding in clinical features and severity. Studies using antisense oligonucleotides revealed a broad phenotypic rescue in transgenic mice. With human clinical trials on the horizon, there is a need to develop clinical outcome measures for MDS. Methods: We surveyed caregivers of MDS individuals to explore the frequency and severity of MDS clinical features, and identify the most meaningful symptoms/domains that need to be included in the outcome measure scales. Results: A total of 101 responses were eligible for the survey. The top six most meaningful symptoms to caregivers in descending order included epilepsy, gross motor, fine motor, communication, infection, and constipation problems. Epilepsy was present in 58.4% of the subjects and 75% were drug‐resistant, Furthermore, ~12% required intensive care unit (ICU) admission. Infections were present in 55% of the subjects, and one‐fourth of them required ICU admission. Constipation was present in ~85% of the subjects and one‐third required enemas/suppositories. Conclusion: Our study is one of the largest cohorts conducted on MDS individuals characterizing the frequency and severity of MDS symptoms. Additionally, these study results will contribute to establishing a foundation to develop parent‐reported outcomes in MDS. Abstract : This survey study is conducted on caregivers of MECP2 Duplication Syndrome to understand the most meaningful symptoms with a goal to develop parent reported outcome measures. Our study is also the first study to investigate the severity of symptoms in MECP2 Duplication Syndrome.